Evaluation of sensory experiments - For tutoring of teachers within restaurant education - Persson, Claes (My University, 2014)
The new curriculum for Swedish restaurant schools now includes education on sensory perception of food. This knowledge is meant to aid the students in combining food and beverages into palatable dishes. This thesis evaluates a number of experiments from a tutorial in the so called Sapere method (Mat för alla sinnen) distributed by the Swedish food agency; the experiments in the tutorial is intended for education of children. The objective of this thesis is to find out if they can be used for higher education combined with theory from a chemistry angle. Several of the experiments proved to be well related to theory collected from a literature study. Some experiments are developed to include more of the theory and some new experiments are tested to give a more extended knowledge. The recommended experiments combined with the theory are considered to be well suited for education on sensory perception of food.
Keywords: Livsvetenskaper; Kemi; Livsmedelsvetenskap; Hushålls- och kostvetenskap; Life Science; Chemical Sciences; Food Science; Domestic science and nutrition